DGK α and ζ Activities Control TH1 and TH17 Cell Differentiation - Yang, Jialong; Wang, Hong-Xia; Xie, Jinhai; Li, Lei; Wang, Jinli; Wan, Edwin C. K.; Zhong, Xiao-Ping (Frontiers in Immunology, 2020)
CD4+ T helper (TH) cells are critical for protective adaptive immunity against pathogens, and they also contribute to the pathogenesis of autoimmune diseases. How TH differentiation is regulated by the TCR's downstream signaling is still poorly understood. We describe here that diacylglycerol kinases (DGKs), which are enzymes that convert diacylglycerol (DAG) to phosphatidic acid, exert differential effects on TH cell differentiation in a DGK dosage-dependent manner. A deficiency of either DGKα or ζ selectively impaired TH1 differentiation without obviously affecting TH2 and TH17 differentiation. However, simultaneous ablation of both DGKα and ζ promoted TH1 and TH17 differentiation in vitro and in vivo, leading to exacerbated airway inflammation. Furthermore, we demonstrate that dysregulation of TH17 differentiation of DGKα and ζ double-deficient CD4+ T cells was, at least in part, caused by increased mTOR complex 1/S6K1 signaling.